Investigation of the Influence of Formed, Non-rotationally Symmetrical Pin Geometries and their Effect on the Joint Quality of Steel and Aluminum Sheets by Direct Pin Pressing - Römisch, David; Kraus, Martin; Merklein, Marion (AJP2021, 2021)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight construction technologies a current trend. For this reason, multi-material systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by using cold formed pin structures has shown to be a process with high potential for joining multi-material systems. These pin structures can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pin structures are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form fit joint. Usually, cylindrical pin structures are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pin structures as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X + Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut is a crucial influence on the joint strength [1], the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined in order to analyze the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension test
Keywords: pin joining; mechanical joining; joining by forming